The Influence Of Sowing Rates And Fertilizers On The Yield Of Durum Wheat Seeds - Azimova M (Zien Journals, 2021)
This article provides data on the influence of sowing rates and fertilizers on the field germination of seeds of durum wheat varieties Krupinka, Zilol and Nasaf. According to the data obtained from the study, it was determined that with an increase in sowing rates, the field germination of seeds of durum wheat varieties decreased.
Keywords: fertilizer; germination; durum wheat